Nghị quyết về cơ cấu tổ chức của Chính phủ nhiệm kỳ Quốc hội khóa XV (Nghị quyết số: 08/2021/QH15) - Quốc hội (2021)
Toàn văn Nghị quyết về cơ cấu tổ chức của Chính phủ nhiệm kỳ Quốc hội khóa XV (Nghị quyết số: 08/2021/QH15)